2017
DOI: 10.1111/andr.12329
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation imprinting errors in spermatogenic cells from maturation arrest azoospermic patients

Abstract: Imprinting errors have been described in spermatozoa from infertile patients with oligozoospermia and azoospermia. However, little is known about methylation of imprinted genes in other spermatogenic cells from azoospermic patients. Therefore, we aimed to evaluate the methylation status of single CpGs located in the differentially methylated regions (DMRs) of two imprinted genes, one paternally (H19) and one maternally (MEST) methylated, in primary spermatocytes of azoospermic patients presenting complete (MAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…DNA extraction for each individual sample was performed according to the protocol described by Marques et al (). Briefly, the sperm pellets were overlaid with 100 μL of lysis solution (10 mM Tris–HCl, 25 mM ethylenediaminetetraacetic acid (EDTA), 1% sodium dodecyl sulfate (SDS), 75 mM NaCl) in the presence of 0.2 mg/mL proteinase K, 50 mM DTT and 0.5 μg glycogen (Invitrogen, Cergy‐Pontoise, France) and incubated overnight at 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction for each individual sample was performed according to the protocol described by Marques et al (). Briefly, the sperm pellets were overlaid with 100 μL of lysis solution (10 mM Tris–HCl, 25 mM ethylenediaminetetraacetic acid (EDTA), 1% sodium dodecyl sulfate (SDS), 75 mM NaCl) in the presence of 0.2 mg/mL proteinase K, 50 mM DTT and 0.5 μg glycogen (Invitrogen, Cergy‐Pontoise, France) and incubated overnight at 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in our studies conducted on testicular sperm, that were individually isolated by micromanipulation from testicular biopsies [6,7], and therefore not contaminated with somatic cells, we have also observed imprinting errors, namely H19 DMR hypomethylation and MEST DMR hypermethylation.…”
mentioning
confidence: 71%
“…Similarly, a study of the methylation status of the paternally imprinted H19 gene and the maternally imprinted MEST gene in spermatogenic cells from azoospermic patients with either complete or incomplete MA revealed the presence of imprinting errors [182]. Low levels of H19 gene methylation were observed in primary spermatocytes and elongated spermatids, and MEST methylation errors were found in spermatocytes [182].…”
Section: Epigenetic Alterations In Azoospermiamentioning
confidence: 99%
“…For example, it has been suggested that miRNAs (essential for spermatogenesis and possibly involved in the regulation of gene expression) are diagnosis biomarkers for azoospermia. Indeed, miRNA expression was altered in patients, relative to controls [179182, 184188]. A recent comparison of men with OA and men with NOA evidenced differences in miRNA expression in spermatogonia, spermatocytes and round spermatids, and thus suggested the presence of epigenetic dysregulation in NOA [189].…”
Section: Epigenetic Alterations In Azoospermiamentioning
confidence: 99%